Advanced Nanostructured All-Waterborne Thiol-Ene/Reduced Graphene Oxide Humidity Sensors with Outstanding Selectivity - Ana Trajcheva, Justine Elgoyhen, Maryam Ehsani, Yvonne Joseph, Jadranka B. Gilev, and Radmila Tomovska (Wiley-VCH GmbH, 2023)
The current-state of polymer-based humidity sensors faces numerous limitations, including energy-costly synthesis, low sensitivity, and slow response times. This study presents innovative approach to overcome these challenges, based on a robust all-water-borne in situ miniemulsion polymerization. The use of water throughout the entire process mitigates the negative environmental impact. Thiol-ene polymers reinforced with reduced graphene oxide (rGO) with concentrations ranging from 0.2–1.0 wt% are selected to fabricate these chemoresistive sensors. The selected thiol-enes present high hydrophobicity and a semicrystalline nature, suggesting resistance to early delamination even under prolonged exposure to humidity. Incorporating rGO not only imparts electrical conductivity but also enhances mechanical and water resistance of the composite films. The 0.6% rGO composite exhibits optimal resistance for humidity sensing, demonstrating rapid and consistent responses across three exposure cycles to water vapor concentrations ranging 800–5000 ppm. Moreover, the sensor exhibits remarkable selectivity toward water vapors over these of toluene, propanol, and 4-methyl-2-pentanol, attributed to the high surface hydrophilicity and inherent porosity of the waterborne film, and network structuring of rGO platelets within the matrix. In summary, this study pioneers a novel approach to polymer-based humidity sensing, addressing key limitations while offering enhanced sensitivity, rapid response times, and superior selectivity.
Keywords: Nanostructured sensors, Thiol-ene polymers, reduced graphene oxide